Cognitive Impairments in Viral Hepatitis Patients: Causes, Manifestations, and Impact on Quality of Life - Tatyana Vasiliyevna Polukchi (Rambam Maimonides Medical Journal)
Viral hepatitis, primarily caused by hepatitis B virus and hepatitis C virus, is widely recognized for its impact on liver function, but emerging evidence suggests it also affects cognitive function. This review explores the causes, manifestations, and impact of cognitive impairments in patients with viral hepatitis, to better understand this often-overlooked aspect of the disease. A literature review was conducted, focusing on studies published in PubMed up to August 2024. Key areas covered include the pathophysiological mechanisms behind cognitive impairment in viral hepatitis, clinical manifestations observed in affected patients, the implications for their daily functioning and overall well-being, and the tools used in cognitive assessments. Common manifestations included deficits in attention, memory, executive function, and psychomotor speed. These cognitive challenges can significantly impact daily activities, occupational performance, and social interactions, contributing to reduced quality of life. Cognitive impairments in viral hepatitis patients represent a significant concern that extends beyond liver health. Recognizing and addressing these cognitive issues are crucial for improving patient outcomes. Enhanced diagnostic strategies and targeted interventions are needed to better manage cognitive symptoms and support affected individuals in maintaining their quality of life. This narrative review aims to enhance clinical practice and inform future research directions.